Pengaruh Financial Literacy dan Self Control terhadap Financial Behavior Pengguna Aplikasi E-Wallet - Shanty Damayanti Hutajulu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The existence of e-wallet applications as a new means for conducting various financial transactions has become a common phenomenon among the public, especially students. These digital wallet applications are gradually replacing cash as the primary medium of exchange and offering quicker financial products/services at users' fingertips. Therefore, as agents of change, Generation Z needs to be equipped with financial literacy and self-control to ensure the use of e-wallets does not deviate and remains aligned with their original purpose, which is to facilitate economic activities. This study examines the influence of financial literacy levels on financial behavior moderated by self-control among active students at Universitas Padjadjaran through a questionnaire distributed across 16 faculties, resulting in a final sample of 442 respondents. The data processing technique used in this study is simple regression analysis and MRA (Moderated Regression Analysis), which aims to understand the influence of independent variables on dependent variables and how the moderating variable strengthens this relationship. The results of this study indicate that financial literacy has a positive and significant effect on financial behavior, and self-control as a moderating factor strengthens the relationship between these two variables.